2020
DOI: 10.1016/j.ymssp.2019.106358
|View full text |Cite
|
Sign up to set email alerts
|

System identification and H-based control of quadrotor attitude

Abstract: The attitude control of a quadrotor is a fundamental problem, which has a pivotal role in a quadrotor stabilization and control. What makes this problem more challenging is the presence of uncertainty such as unmodelled dynamics and unknown parameters. In this paper, to cope with uncertainty, an H ∞ control approach is adopted for a real quadrotor. To achieve H ∞ controller, first a continuous-time system identification is performed on the experimental data to encapsulate a nominal model of the system as well … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 46 publications
0
12
0
3
Order By: Relevance
“…Other researchers implemented the H ∞ controller for the quadcopter system because of its robustness in rejecting the model uncertainties and external disturbances. Noormohammadi-Asl et al [88] suggested a H ∞ controller for a quadcopter model to cope up with the unmodeled dynamics and unknown parameters. The experimental results indicated the robustness of the designed controller in providing better tracking performance compared to a well-tuned PID and μ synthesis controllers.…”
Section: Quad-rotor Systemsmentioning
confidence: 99%
“…Other researchers implemented the H ∞ controller for the quadcopter system because of its robustness in rejecting the model uncertainties and external disturbances. Noormohammadi-Asl et al [88] suggested a H ∞ controller for a quadcopter model to cope up with the unmodeled dynamics and unknown parameters. The experimental results indicated the robustness of the designed controller in providing better tracking performance compared to a well-tuned PID and μ synthesis controllers.…”
Section: Quad-rotor Systemsmentioning
confidence: 99%
“…are the regression matrices of known functions, and Θ ∈ R 7 is the parameter vector. The implementation of the discrete filtering schemes is performed in MATLAB by using the function filter(b,a,x), where b and a represents row vectors containing the coefficients for the numerator and denominator either of the transfer functions (35) or (36), respectively, and x represents the signal to be processed. In order to reject the high-frequency noise components from the measured signals and avoiding to lose important information from the system dynamics, the cut-off frequency of the filter must be selected considering the highest frequency from the system excitation signals, see [25] and [58].…”
Section: ) Filtered Regression Model Constructionmentioning
confidence: 99%
“…Comparisons between a PID scheme and an internal model control were given. Parameter identification for a continuous-time black-box model of a quadrotor was achieved in [35].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, synthesis of several high-efficiency nonlinear control schemes may require accurate mathematical models or have a complex structure, which complicate their implementation in realistic systems due to some variables and parameters are unavailable or hard to obtain [9]. us, the Active Disturbance Rejection Control (ADRC) methodology constitutes an excellent alternative to achieve robustness against a wide class of disturbances [10].…”
Section: Introductionmentioning
confidence: 99%